Understanding population genetics - Sall, Torbjorn; Bengtsson, Bengt O. (Wiley-Blackwell, 2017)
An inspiring introduction to a vital scientific field. The reader is taken through ten mathematical derivations that lead to important results, explaining in a hands-on manner the key concepts and methods of theoretical population genetics. The derivations are carefully worked out and easy to follow. Particular attention is given to the underlying assumptions and the mathematics used. The results are discussed and broadened out with relevant current implications. All topics feature questions with helpful answers. The book is intended for the reader who already knows some population genetics but requires a more comprehensive understanding. It is particularly suited to those who analyse genetic data and wish to better grasp what their results actually mean. It will also be helpful for those who wish to understand how population genetics contributes to the explanation of evolution. Or as the writers claim: If one wants to understand life in all its improbable and amazing richness one must start by understanding population genetics. -- Provided by publisher.